The role of women in promoting peaceful and societal coexistence at the current stage - Iraq as a model - Assistant. Prof Dr. Abeer Najm Abdullah Al-Khalidi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The role of women in promoting peaceful and societal coexistence at the current stage - Iraq as a model